2018
DOI: 10.2478/acph-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Catha Edulis Active Principle, Cathinone, Suppresses Motor Coordination, Accelerates Anxiety and Alters the Levels of Dopamine and its Metabolites in the Limbic Areas of Male Swiss Albino Mice

Abstract: Cathinone, the active principle of khat (Catha edulis), stimulates, excites and produces euphoric feelings in khat users. Locomotor and rearing activities, either individual or in groups, of male Swiss albino mice were decreased significantly compared to the control. Motor coordination tests (rotarod, rope climb and grip tests) have shown decreased motor performance in the mice treated with cathinone compared to the control. The elevated plus maze test has shown significant anxiety in the mice compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Effects of khat on dopamine (27), glutamate, and GABA transmissions (29,30) could be contributed to the lower psychomotor and anxiety-like effects of Ke in this current study. According to studies conducted before, the administration of monosodium glutamate, which increases glutamate levels in the body, reduced the number of open-arm entries and duration in EPM test (31) and showed anxiety-like symptoms (32).…”
Section: Discussionmentioning
confidence: 58%
“…Effects of khat on dopamine (27), glutamate, and GABA transmissions (29,30) could be contributed to the lower psychomotor and anxiety-like effects of Ke in this current study. According to studies conducted before, the administration of monosodium glutamate, which increases glutamate levels in the body, reduced the number of open-arm entries and duration in EPM test (31) and showed anxiety-like symptoms (32).…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, the effect of clavulanic acid was prevented by additional treatment with DHK, suggesting GLT-1 to be involved in this attenuation. Bedada et al showed a similar increase in anxiety behaviors among mice receiving 200 mg/kg of khat extract [48], and another study reported cathinone treatment at doses of 1.25 and 2.5 mg/kg for 14 days to induce anxiety-like behaviors [49]. Mohebbi et al likewise used a rat model to evaluate the effect of clavulanic acid on alcohol withdrawal symptoms, including anxiety.…”
Section: Discussionmentioning
confidence: 95%
“…Cathinone, the natural amphetamine-like composition in Catha edulis with the highest levels in stems and young leaves, was proved to play a major role in this euphorising plant ( Kalix, 1996 ; Alsanosy et al, 2020 ; Dhabbah, 2020 ). Some studies identified mechanisms of cathinone on the central nervous system in changing presynaptic striatal dopamine system and interfering with pituitary cell integrity in vervet monkeys ( Nyongesa et al, 2014 ; Nyongesa et al, 2015 ), altering levels of dopamine and its metabolites and accelerating oxidative stress in limbic areas of swiss albino mice ( Sathi et al, 2014 ; Safhi et al, 2018 ), inhibiting monoamine (dopamine, norepinephrine, etc) reuptake in human nerve cells ( Bredholt et al, 2013 ), inducing striatal c-fos expression in Siberian hamster ( Jones et al, 2014 ), and other complex mechanisms of psychosis caused by Catha edulis use ( Odenwald et al, 2005 ; Bredholt et al, 2013 ). The network, combined with the co-occurring keywords, demonstrated the progress and correlation of the original research of Catha edulis at a global level via bibliometric mapping.…”
Section: Discussionmentioning
confidence: 99%